Fatal haemorrhage from an aortoesophageal fistula secondary to button battery ingestion in a 15-month-old child. Case report and literature review. (July 2020) - Karnecki, Karol; Pieśniak, Dorota; Jankowski, Zbigniew; Gos, Tomasz; Kaliszan, Michał
Highlights: The ingestion of a round button battery may be dangerous for a child and may be a medicolegal issue regarding child care. Autopsy and histopathological examination may provide relevant information regarding the cause and mechanism of death in case of foreign object like button battery ingestion. The establishment of the exact time period between battery ingestion and the occurrence of the complication is often impossible. If a child is suspected of having ingested a battery, professional medical assistance is urgently required. Abstract: Small children put various objects into their mouths, which is one of their ways of exploring the surrounding world. Apart from toy parts, e.g. Lego® bricks or magnetic spheres, such objects include coins, small stones, as well as batteries used for different electric devices. Such batteries, especially the flat, round button type, may be ingested and become impacted in one of the physiological narrowing sites of the oesophagus, leading to serious complications. The case of a 15-month-old child is presented, who died due to a massive gastrointestinal haemorrhage from an aortoesophageal fistula that developed at the site of a pressure ulcer caused by an impacted button battery. The presented case shows that ingestion of even a small battery may lead to death. The asymptomatic course of the battery ingestion significantly hinders both the assessment of circumstances and the time of the battery ingestion. Sudden death may result from a massive haemorrhage from a pressure-induced injury to a big blood vessel.